CONFLITS FONCIERS ET GESTION DES PLANS D’EAU IVOIRIENS : CAS DE LA LAGUNE OUEST ÉBRIE - Narcisse, Aboya (European Scientific Journal, ESJ, 2014)
Conflicts between different actors operators in the water bodies of the Ivory Coast, including, the lagoon Ébrié have been registered. This paper seeks to know the usage conflicts existing on the Western part of the lagoon Ébrié, lined essentially adjoukrou, near Dabou. Apart from the village of Layo, where we meet a few foreigners who practice fishing, the waters of this region of the country are owned and operated by the aboriginal people. This has the consequence, the recording of very little conflict. Notwithstanding, new forms of fishing techniques, such as the acadja, are a source of dissension between traditional fishermen and acadjaculteurs in the villages of Kpass and Mopoyème. The scope of this article is drawn to the attention of the state authorities and administrative these conflicts "minor" in this part of the country, in order to prevent them. And, for the scientific community to fill a gap on this issue, which too often is known that by the voice of the mass-media.